Risk of chemotherapy-induced febrile neutropenia with early discontinuation of pegfilgrastim prophylaxis: a retrospective evaluation using Medicare claims. (3rd April 2019) - Weycker, Derek; Hanau, Ahuva; Lonshteyn, Alexander; Bowers, Charles; Garawin, Tamer; Bensink, Mark; Chandler, David
Abstract: Background: Two recent evaluations reported that many cancer chemotherapy patients discontinue pegfilgrastim prophylaxis (PP) following the first cycle, and that these patients have a higher subsequent risk of febrile neutropenia (FN). Such evidence is based principally on the experience of younger adults with private healthcare coverage, and the generalizability of results to elderly Medicare patients is unknown. Methods: A matched-cohort design and data from the Medicare Claims Research Identifiable Files were employed. The source population comprised cancer patients aged ≥65 years who received chemotherapy with intermediate/high-risk for FN and first-cycle PP. From the source population, beginning with the second cycle, all patients who received PP in all previous cycles were identified. From this sub-set, patients who did not receive PP in the cycle of interest ("comparison patients") were matched to those who received PP in that cycle ("PP patients"); the same process was repeated for subsequent cycles. Odds ratios (OR) for FN (broad and narrow definitions) were estimated using generalized estimating equations. Results: Among 77, 616 elderly patients in the source population, 5.3% did not receive second-cycle PP and were matched to those who did. In cycle 2, FN odds were significantly higher among comparison patients vs PP patients when employing the broad definition (OR = 1.9, p < .001) and the narrow definition (OR = 2.1, p < .001). Results for subsequent cycles (broad definition: OR = 2.0, p < .001; narrow definition: OR = 2.1, p < .001) and for the last cycle (broad definition: OR = 1.4, p = .060; narrow definition: OR = 1.7, p = .055) were largely comparable. Conclusions: In this large-scale evaluation of elderly Medicare patients who received myelosuppressive chemotherapy and first-cycle PP in recent US clinical practice, FN risk was substantially lower among patients who continued to receive PP in subsequent cycles vs those who discontinued PP.